Pengelolaan Fasilitas di Daya tarik Wisata Pincuran Tujuh Kabupaten Sijunjung - Fitri Handayani; yuliana luliana (Departemen Pariwisata Universitas Negeri Padang, 2023)
The background of this research is the management of facilities at Pincuran Tujuh tourist attraction in Sijunjung Regency. Pincuran Tujuh tourism Attraction is one of the artificial tourist attraction found in Sijunjung Regency. This Study aims to determine the management of facilities in Pincuran Tujuh Tourism Attraction, Sijunjung Regency. The research is included in the type of descriptive research with qualitative data. Data collection techniques were carried out through the use of interview, observasion, and documentation method and data analysis using data reduction, data persetation, and drawing conclusions. The research is viewed from three indicator namely, main facilities, and supporting facilities. The result is study describe the management of exiting facilities in Pincuran Tujuh Tourism Attraction, Sijunjung Regency based on management functions wicht include planning, organizing, actuating and controlling. Judging from the indicators of the main facilities, there already planning, organization, mobilizing and supervising but it has not been going well. Then is terms of indicators of supporting facilities threre is no planning, organization alredy exists but has not been realized, mobilization already exists, and supervision already exists. After that, in terms of supporting facilities, there is already planning, organization, mobilization and supervision